Cultural enterprises as an alternative for local development - Montiel Ensuncho, Anibal; Vásquez López, Lenys Esther (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The business sector in Colombia has experienced processes such as globalization, the covid-19 pandemic, tax reforms, which articulated results in excessive competition, uncertainty and crisis in economic terms and the cultural entrepreneurs of the municipality of Monteria do not escape this. In this order of ideas, the objective of this research work aims to analyze the potential of cultural business units to generate alternatives for local development.